Mapping of Mango Trees in Crisis Land With Web-Based GIS Applications - Mohamad Fatkhur Rozi; Zulfikar Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
ABSTRACT Mango trees are one of the fruit plants capable of growing in a critical, and often used for conservation. This study aims at mapping mango trees in the northern region of Jombang Regency. In an effort to help the community to get to know mango trees, a web-based mapping system is created using JS, XAMPP, and PHPMySQL software. This research was conducted with several stages in the system of systems, namely secondary and primary data collection which will be used for the system database. The results of this study have been designed a web-based mango plant mapping application that will provide information for the community and related agencies in finding data and mango fruit. The results of a poll of 30 respondents showed that 92% were enthusiastic about using this application so that the web-GIS application was in demand by the public. Keywords: Web-based GIS mapping, mango trees, critical landt.